Development and validation of perceived sexual resentment scale for women (PSRS-W) - Syeda Ayat-e-Zainab Ali; Wardah Ishfaq; Bushra Hassan; Nazia Iqbal (Journal of the Pakistan Medical Association, 2021)
Objective: To develop a valid and reliable scale to asses perceived sexual resentment among married women. Method: The cross-sectional validation study was conducted from September 2018 to July 2019 at the International Islamic University, Islamabad, Pakistan, and had three phases. Phase I comprised initial generation/selection of items regarding sexual resentment among married women. Phase II comprised pilot testing of the perceived sexual resentment scale for women items before applying the scale on the actual sample. Phase III determined convergent validity by estimating correlation of the newly developed scale with the Sexual Coercion in Intimate Relationship Scale, and its divergent validity by finding correlation with the Satisfaction with Life Scale. Data was analysed using SPSS 23. Results: The pilot study, done on 20 married women, established the internal consistency of the newly developed scale (?=0.82). Overall, three factors emerged following factor analysis. The scale had 29 items and reliability analysis of the entire scale indicated adequate internal consistency (?=0.93). The convergent validity of the scale and the Sexual Coercion in Intimate Relationship Scale was positive (p<0.001), and the correlation with the Satisfaction with Life Scale was negative (p<0.01), indicating that the newly-developed instrument had a good convergent and divergent validity. Conclusion: The Perceived Sexual Resentment Scale for Women was found to be a precise and concise 29-item self-reporting tool developed to assess sexual dislikes and displeasures among married women. Continuous....